ANALISIS PERAN GURU DALAM MEMBANGUN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN JASMANI, OLAHRAGA, DAN KESEHATAN DI MTs MINHAJUTTHULLAB TUNDAGAN - Ardiansyah, Rifa; Alfiah Rizqi Azizah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe and analyze the teacher's role in fostering student learning motivation during Physical Education, Sports, and Health (PJOK) lessons at MTs Minhajuthullab Tundagan, as well as to identify the factors supporting and hindering this process. A qualitative approach was employed, involving the PJOK teacher and Grade IV students as subjects. Data were collected through observation, interviews, and documentation, and subsequently analyzed using the Miles and Huberman model, which encompasses data reduction, data display, and conclusion drawing. The results indicate that the teacher acts as a motivator, facilitator, guide, and evaluator by providing verbal encouragement, employing varied teaching methods, offering reinforcement, and creating an active, enjoyable learning atmosphere. Student learning motivation was found to be in the "very good" category, characterized by enthusiasm, active participation, cooperation, and a resilient attitude during lessons. Supporting factors include students' internal motivation, environmental support, and teacher strategies, whereas inhibiting factors include differences in student characteristics, low self-confidence, and limited learning facilities and infrastructure.